Array CGH in patients with learning disability (mental retardation) and congenital anomalies: updated systematic review and meta-analysis of 19 studies and 13,926 subjects - Sagoo, Gurdeep S; Butterworth, Adam S; Sanderson, Simon; Shaw-Smith, Charles; Higgins, Julian P T; Burton, Hilary (Genetics in medicine, 2009)
: Array-based comparative genomic hybridization is being increasingly used in patients with learning disability (mental retardation) and congenital anomalies. In this article, we update our previous meta-analysis evaluating the diagnostic and false-positive yields of this technology. An updated systematic review and meta-analysis was conducted investigating patients with learning disability and congenital anomalies in whom conventional cytogenetic analyses have proven negative. Nineteen studies (13,926 patients) were included of which 12 studies (13,464 patients) were published since our previous analysis. The overall diagnostic yield of causal abnormalities was 10% (95% confidence interval: 8–12%). The overall number needed to test to identify an extra causal abnormality was 10 (95% confidence interval: 8–13). The overall false-positive yield of noncausal abnormalities was 7% (95% confidence interval: 5–10%). This updated meta-analysis provides new evidence to support the use of array-based comparative genomic hybridization in investigating patients with learning disability and congenital anomalies in whom conventional cytogenetic tests have proven negative. However, given that this technology also identifies false positives at a similar rate to causal variants, caution in clinical practice should be advised.